Education as a Strategic Pathway for Social Justice and Equity through Institutional Governance and Community Engagement - Mahesa, Abdi; Arfandi, Rizal; Baktiar, Baktiar (Journal Social Humanity Perspective, 2024)
Since the time of ancient civilization, education has been perceived as an effective channel of promoting social justice and equity, but its contributions have been debatable both in its ability to deconstruct inequalities and its propensity to replicate them. This paper addresses the issue of how education can be used as a transformative tool once equity is used as its core strategy. Using a qualitative method, the study involves teachers, students, parents, administrators, and policymakers in the form of interviews, focus group discussions, classroom observations, and an analysis of documents. The results point to a number of problems that frustrate the good intent of education such as the lack of resources, social discrimination, and unfair policy structures. In the meantime, the study finds the following potentially promising practices to be included: school-community collaboration and affirmative action programmes and teacher training in inclusive pedagogy to be indicators that not only is structural change possible, but also sustainable. The discussion highlights the managerial relevance of making equity central to organizational systems of education, which require redistributive resource policies, culturally responsive leadership, curriculum audits, policy customization, and ethical integration of technology. The study emphasises the importance of understanding equity as an ethical necessity and a strategic necessity by perceiving education as a disciplined institution rather than an apolitical social production. The article also adds to the academic literature on management by providing the framework in which social justice can be used as a measure of institutional legitimacy and efficiency. Lastly, the question of whether education can develop justice, is determined not only by what is desired but also the strategic design of systems, policies and practices aimed at justice, inclusivity and democratic sustainability.